A preliminary evaluation of a new GeneXpert (Gx) molecular point-of-care test for the detection of Trichomonas vaginalis. (23rd December 2015) - Badman, S G; Causer, L M; Guy, R; Tabrizi, S N; Francis, F; Donovan, B; Whiley, D
Abstract : Objectives: Global concerns regarding the prevalence, asymptomatic nature and burden of disease associated with Trichomonas vaginalis (TV) continue. The lack of a portable molecular point-of-care assay to detect this infectious disease has meant that many remote or low-resource settings still need to rely on delayed results from central laboratories and/or syndromic management as treatment strategies. We evaluated the new GeneXpert (Gx) TV nucleic acid amplification test (NAAT) compared with an in-house laboratory NAAT to determine whether it would be suitable for use at the point of care. Methods: In a state-based laboratory and using their in-house NAAT, we selected the first 60 urine samples that were positive and the first 60 that were negative (n=120) in the study period for Gx TV testing in order to reduce collection delays and avoid the freezing of samples. Results: Positive percentage agreement between the Gx TV and NAAT was 95.0% (95% CI 86.1% to 99.0%), negative percentage agreement was 100.0% (95% CI 93.5% to 100.0%) and overall percentage agreement was 97.4% (95% CI 92.5% to 99.5%). Three discordant results were detected with each being close to the cycle threshold of detection using the in-house NAAT assay. Conclusions: Findings suggest the Gx TV assay is easy to use and has suitable overall agreement for sexually transmissible infection (STI) testing at the point of care. It may be used in combination with the Gx CT/NG assay to test for all three STIs simultaneously using this portable and modular-based NAAT platform.